Aesthetics and the Economic Beauty of Socialism. (1st October 2019) - Li, Linan
Abstract : Some scholars have studied economic beauty with the lack of overall, systematic ideas. Basing on the previous research, this article focuses on the economic beauty and socialist economic beauty, and discusses the concept and characteristics of economic beauty. According to the definition and characteristics of economic beauty, the alienation of economic beauty appears in capitalist economic activities, which is rooted in capitalist production relations, and existed in its economic activities. Socialist economy avoids the problem of alienation of capitalist economic beauty. The value, humanistic care, and belief in truth, goodness and beauty in socialist economy are of great theoretical and practical significance.